Negotiating The Politics of Citizenship of Baha`I In Indonesia - Haris Fatwa Dinal Maula (Indonesia Social Justice Network (ISJN), 2022)
This research portrays and discusses the Baha`is struggle in political and social life after the Constitutional Court 2016 decision. Baha`i from its inception was often under pressure from the government. It was considered deviant teaching by the Iranian government rather than as an independent religion, where the Baha`i first emerged. Not much different, arriving in Indonesia, Baha`i was also presented as a splinter sect of Islam. That implicates the difficulty of the Baha`i in positioning their adherents in social and legal life in Indonesia. This research briefly reveals the social and political position of Baha`i followers after Constitutional Court Decision No. 97 / PUU / XIV/ 2016 regarding administrative law No. 23/ 2006 and Law No. 24/ 2013. This study uses Kristian Stokke's theory of politics of citizenship. It discerns the imperative elements in a society so that it can be called full citizenship which all of its socio-political rights can be well-fulfilled. This research finds that since first spread in Indonesia, until administrative law which has been revised several times, the Baha`i has a dynamic of accessing adequate civil rights services. However, the decision to empty the religion column on the ID card seems to have two different sides, whether it potentially perpetuates the stigma that Baha`is who are not in line with Pancasila principles, in the other side it has the potential to be a moment to attract someone's attention to ask about Baha’i